Analisis Sistem Pengendalian Internal Atas Pembayaran Dana Pensiun pada PT. Taspen Persero KCU Medan - Aninda Zahra; Hendra Harmain; Wahyu Syarvina (Jurnal Riset Ekonomi dan Akuntansi, 2024)
The purpose of this study is to know the implementation of internal control over the payment of pension funds, to find out the procedures for distributing pension funds, and to find out improvements that can be implemented in internal control in the future at PT. Taspen (Persero) KCU Medan. This research method uses qualitative methods with interviews, observation and documentation. The subjects of this research were the head of the financial treasurer and employees of the financial accounting department as well as several pension participants at PT. Taspen Persero KCU Medan. This first result shows that the implementation of the control system and internal procedures has been implemented according to the applicable SOP but there are still delays in salary payments by paying partners due to a lack of information and communication which results in customers complaining about these delays. The results of the second research state that the data recorded in e-dapem and e-karip, especially data on pension dependents, is often not up to date, this condition causes internal parts such as cash to often experience shortages in payment of civil servant pension funds, even in pension payments through transfers. it takes a long time and produces less accurate information.